2016
DOI: 10.5603/kp.a2015.0158
|View full text |Cite
|
Sign up to set email alerts
|

Balloon aortic valvuloplasty — ups and downs — are we facing a procedure comeback?

Abstract: A b s t r a c t Background:Recently, there has been renewed interest in balloon aortic valvuloplasty (BAV). Aim:To analyse the indications and short-term outcome of BAV since transcatheter aortic valve implantation (TAVI) was launched in our institution. Methods:Between September 2010 and September 2014, 25 consecutive patients (19 female, 6 male) underwent BAV. The mean age was 72 ± 11.4 years, mean EuroScore II was 10.4 ± 11.7%, mean logistic EuroScore 23.5 ± 23.6%, mean Society of Thoracic Surgeons mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Death were classified as cardiovascular in 14 (73.7%) cases (recurrent heart failure, sudden death, major stroke, pulmonary embolism) and noncardiovascular in 5 (26.3%) cases (cancer, major gastrointestinal bleeding). Patients who were treated with BAV due to cardiogenic shock had the worst prognosis with 100% mortality in this group . Mortality rate was also high among palliative patients n = 9 (41%).…”
Section: Resultsmentioning
confidence: 85%
“…Death were classified as cardiovascular in 14 (73.7%) cases (recurrent heart failure, sudden death, major stroke, pulmonary embolism) and noncardiovascular in 5 (26.3%) cases (cancer, major gastrointestinal bleeding). Patients who were treated with BAV due to cardiogenic shock had the worst prognosis with 100% mortality in this group . Mortality rate was also high among palliative patients n = 9 (41%).…”
Section: Resultsmentioning
confidence: 85%
“…On further review of the in-hospital mortality group occurring within the first decade at this institution, all were associated with vascular complications resulting in excessive bleeding. Similarly, other studies have reported this complication along with other serious outcomes including stroke, acute aortic regurgitation, and myocardial infarction in 10-20% or more of patients [18,[19][20][21][22]. With improvements in vascular closure devices, patient outcomes have improved.…”
Section: Discussionmentioning
confidence: 75%
“…Except for Debry and colleagues’ work, which is the latest study, all previous papers present no more than two dozen patients in single-center studies, while using different definitions for cardiogenic shock and employing logistic Euroscore for patient characterization, instead of the more recent Euroscore II. Olasinska-Wisniewska and colleagues also report cases of patients in cardiogenic shock using the latest Euroscore II, although they make no distinction between patients with cardiogenic shock and pulmonary edema due to severe heart failure [23]. Some report the peak aortic gradient change while others report the mean aortic gradient change after BAV.…”
Section: Discussionmentioning
confidence: 99%